Implicaciones de la deforestación e incendios forestales en la distribución potencial de especies forestales de aprovechamiento condicionado del bosque andino ecuatoriano - Puchaicela Tambo, Diana Elizabeth (2024)
Andean forests are found throughout the Andes Mountains, ecosystems that are home to a great diversity of species and provide vital benefits for people, such as water management, soil protection, carbon sequestration, and scenic value. However, worldwide, as in Ecuador, deforestation and forest fires cause irreversible damage. The present study is situated in the scenario of the loss and degradation of the Ecuadorian Andean Forest, an ecosystem of high ecological and socioeconomic relevance. The purpose of this research is to contribute to scientific knowledge about the consequences of these threats on the potential distribution of conditional-use forest species, for example, those that depend on sustainable management for their conservation and use. The potential distribution of five species (Mauria heterophylla, Myrcianthes rhopaloides, Polylepis incana, Vallea stipularis and Weinmannia elliptica) was determined. Presence points and climatic variables were obtained to estimate the potential distribution. Records with no coordinates, repeated coordinates, null values, altitudinal anomalies, and climatic heterogeneity were eliminated. Then the calibration areas were created and the variables were chosen. Then the best models are generated and selected considering the statistical significance of partial ROC, and omission rate E= 5%, and model complexity (AICc). Finally, the final models are reviewed by specialists. Fire and vegetation cover information is used to determine the potential distribution areas affected by deforestation and forest fires. Data from active fires with <30% confidence, areas of volcanic activity, and areas with anthropogenic presence were eliminated. The original forest vegetation was chosen to estimate the loss of forest area and to make an intersection with the suitability zones. By intersecting the active fires with the areas of suitability. Finally, Mauria heterophylla is a species that adapts to the climatic and edaphic conditions of the mountainous areas of the Andes. Its potential distribution is concentrated on the eastern and western slopes of this mountain range, where it finds optimal levels of humidity, temperature, and nutrients for its development. The species does not currently occupy the entire suitability area. Myrcinathes rhopaloides shows greater suitability on the western slopes of the Andes, from Carchi to Loja, Polylepis incana shows greater suitability in the central and northern highlands of the country. Vallea stipularis shows high suitability in a large part of the inter-Andean range, in the province of Loja, Weinmannia elliptica 5 shows suitability along the eastern and western foothills of the Andes. The species most affected by deforestation and forest fires is Myrcianthes rhopaloides, with a loss of 18.85% of its native forest in its adaptation area. During the period between 1990 and 2000, 1605 (AF) were recorded associated with this species. In second place, Mauria heterophylla shows a loss of 15.25% of its natural habitat.